Seeing the Inner from Outer - Yoga Yuniadi (Jurnal Kardiologi Indonesia, 2013)
Since Furchgott et al1 showed that acetylcholine requires the presence of endothelial cells to induce vasodilation, the importance of the endothelial cell layer for vascular homeostasis has been increasingly appreciated. Endothelial dysfunction was initially identified as impaired vasodilation to specific stimuli such as acetylcholine or bradykinin. A broader understanding of the term would include not only reduced vasodilation but also a proinflammatory and prothrombic state associated with dysfunction of the endothelium.2 Figure 1 describe regulation function of endothelium during normal and dysfunction condition.3 In human, endothelial dysfuntion was first described in forearm of hypertensive patient.4 Dysfunction of the endothelium has been attributed to the pathophysiology of different forms of cardiovascular disease, including hypertension, coronary artery disease, chronic heart failure, peripheral artery disease, diabetes, and chronic renal failure.2